Conductometric Assisted ZnO and Polypyrrole Composite Based \(NH_3\) Gas Sensor - Gahlot, Ajay Pratap Singh (Fundamental Research and Application of Physical Science Vol. 4, 2023)
Metal oxides are excellent choices as base materials in emerging technologies in the field of Gas Sensors. In this work, an effort is made to prepare the ZnO and polypyrrole composite thin film using sol-gel technique. Nanocomposite thins film was prepared using spin coating on glass substrates for ammonia gas sensing. ZnO and polypyrrole sols were prepared using sol-gel technique and thin films were prepared by using spin coater. The nanocomposite thin films were prepared by varying the percentage composition of ZnO and Polypyrrole. Structural, optical and morphological properties of the prepared films were done using XRD, UV-Visible and SEM studies. The films were separately prepared on Inter-Digital Transducers for gas sensing applications. Gas sensing response characteristics of the prepared sensor were performed using laboratory. The sensing response of the prepared films is observed and found to be maximum (~33) for the 70%PPy+30%ZnO film at a relatively low operating temperature of about 150 °C. The prepared film is also tested by optical gas sensing technique i.e., Surface Plasmon Resonance (SPR). SPR gas sensor works on the principle of recording the change in refractive index of the sensing layer (70%PPy+30%ZnO) on exposure to target ammonia gas.